Karakterisasi Induk Pembentuk Populasi G0 Sintetis Udang Galah Dari Sumber Genetik Sungai Barito, Kintap Dan Pagatan - Ani Rimalia; Mukhlisah Mukhlisah; Yulius Kisworo (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2015)
This research knowing character of Parental Sheper G0 Syntetic Population of The Giant Fresh Water Prawn from genetic resources of Barito, Kintap and Pagatan River. The results of the research showed character of morfometric body weight, Abdoment wide, Tinggi Badan, Thorax length, Uropoda langth, Total length of Pagatan genetic resources is the best with Kintap and Barito genetic resources. While character of morfometric Abdoment length from Pagatan genetic resources is the best with Barito and Kintap genetic resources. Than character of morfometric Telson length from Barito genetic resources is the best with Kintap and Pagatan genetic resources and so character of Anatomy and Coloring Pattern of The Giant Fresh water Prawn not a diffirent.